Reassessment of the succession of lactic acid bacteria in commercial cucumber fermentations and physiological and genomic features associated with their dominance. (May 2017) - Pérez-Díaz, I.M.; Hayes, J.; Medina, E.; Anekella, K.; Daughtry, K.; Dieck, S.; Levi, M.; Price, R.; Butz, N.; Lu, Z.; Azcarate-Peril, M.A.
Abstract: A compositional re-assessment of the microbiota present in commercial cucumber fermentation using culture independent and dependent methods was conducted, with emphasis on lactic acid bacteria (LAB). Two commercial cucumber fermentation tanks were monitored by measuring pH, dissolved oxygen and temperature, and used as sources of samples for microbial plating, genomic DNA extraction and measurement of organic acids and carbohydrates by HPLC. Six additional commercial tanks were included to identify the dominant microorganisms using molecular methods. A comparative analysis of the publically available genome sequences corresponding to the LAB found in cucumber fermentations was completed to gain an understanding of genomic features possibly enabling dominance. Analyses of the microbiota suggest Lactobacillales prevail in cucumber fermentations, including in order of prevalence Lactobacillus pentosus, Lb . plantarum, Lb . brevis, Weissella spp., Pediococcus ethanolidurans, Leuconostoc spp. and Lactococcus spp. It was observed that Lb . pentosus and Lb . plantarum have comparatively larger genomes, higher gene counts, uniquely distribute the ribosomal clusters across the genome as opposed to close to the origin of replication, and possess more predicted amino acids prototrophies and selected biosynthesis related genes. It is theorized that Lb . pentosus and Lb . plantarum dominance in cucumber fermentations is the result of their genetic make-up. Highlights: Lactobacillus pentosus prevails in commercial cucumber fermentations. L . plantarum, L . brevis, Weissella, P. ethanolidurans, Leuconostoc and Lactococcus are also present in cucumber fermentations. L . pentosus and L . plantarum have genomic features that are comparatively advantageous for dominance in cucumber fermentations.